Significance of coagulase negative staphylococci in neonates with late onset septicemia - Bansal, Seema; Jain, Amita; Agarwal, Jyotsna; Malik, G K (Indian journal of pathology & microbiology, 2004)
Present study was undertaken for establishing significance of coagulase negative staphylococci isolated from cases of late onset neonatal septicemia. 660 neonates admitted to NICU with clinical suspicion of late onset septicemia, over a period of nine months, were included in study. After skin preparation 1.5-ml blood for culture was collected from two different sites by venipuncture and each was inoculated into a blood culture bottle. All CONS thus isolated were further analysed. Laboratory criteria for significant CONS bacteremia was defined as recovery of CONS with in 48 hours of specimen collection from both sites of a blood culture set that displayed uniform antibiotic susceptibility and biochemical reactions. Due to technical difficulties two samples for blood culture were obtained only from 338 cases, CONS were recovered from 52 (22.7%) cases; only 13 (25%) were considered significant. Only single blood sample was available from remaining 322 subjects and CONS were recovered from 36/322 (24.3%). CONS isolation rate was similar in both subject groups. Using double specimen protocol we found majority of CONS recovered from neonates, to be probable contaminants. Recovery of CONS from blood of a septicemic neonate needs to be viewed with caution since not all of them are true bacteremic agents.